The endocannabinoid transport inhibitor AM404 differentially modulates recognition memory in rats depending on environmental aversiveness - Campolongo, Patrizia; Ratano, Patrizia; Manduca, Antonia; Scattoni, Maria Luisa; Palmery, Maura; Trezza, Viviana; Cuomo, Vincenzo (Frontiers in Behavioral Neuroscience, 2012)
Cannabinoid compounds may influence both emotional and cognitive processes depending on the level of environmental aversiveness at the time of drug administration. However, the mechanisms responsible for these responses remain to be elucidated. The present experiments investigated the effects induced by the endocannabinoid transport inhibitor AM404 (0.5–5 mg/kg, i.p.) on both emotional and cognitive performances of rats tested in a Spatial Open Field task and subjected to different experimental settings, named High Arousal (HA) and Low Arousal (LA) conditions. The two different experimental conditions influenced emotional reactivity independently of drug administration. Indeed, vehicle-treated rats exposed to the LA condition spent more time in the center of the arena than vehicle-treated rats exposed to the HA context. Conversely, the different arousal conditions did not affect the cognitive performances of vehicle-treated animals such as the capability to discriminate a spatial displacement of the objects or an object substitution. AM404 administration did not alter locomotor activity or emotional behavior of animals exposed to both environmental conditions. Interestingly, AM404 administration influenced the cognitive parameters depending on the level of emotional arousal: it impaired the capability of rats exposed to the HA condition to recognize a novel object while it did not induce any impairing effect in rats exposed to the LA condition. These findings suggest that drugs enhancing endocannabinoid signaling induce different effects on recognition memory performance depending on the level of emotional arousal induced by the environmental conditions.